Penggunaan Informasi Anggaran dan Keuangan oleh Politisi di Parlemen - Yelia Findy Tiara; Deviani Deviani (Universitas Negeri Padang, 2024)
This research aims to find out how budget and financial information is used by politicians in parliament (case study of the Regional People's Representative Council (DPRD) Agam District). This research is qualitative research using a descriptive approach. This research emphasizes processes and meanings that are not measured but places more emphasis on the socially constructed nature of reality, the close relationship between the researcher and the subject and forming an investigation that contains value. Researchers for this research collected data through interviews with members of the Agam Regency DPRD. The results of this research state that budget and financial information is really needed, but Agam District DPRD members have not been able to use these reports optimally. There is still little research on the use of budget and financial information by members of the Regional People's Representative Council (DPRD). And the researchers conducted research in the Agam Regency area, where in this area the research carried out by the researchers was something new. This research has a contribution in that, based on the research results, it can improve the work patterns or composition of DPRD members in the budget sector, so that it can create a better budget